2001
DOI: 10.1111/j.1467-842x.2001.tb00549.x
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of risk factors for asthma in New Zealand children

Abstract: Objective : As in other English‐speaking countries, asthma is a major and increasing health problem in New Zealand. This study examined the risk factors for asthma in children aged 7–9. Methods : Cases and controls were randomly selected from participants in the Wellington arm of the International Study of Asthma and Allergies in Childhood (ISAAC). Cases were children with a previous diagnosis of asthma and current medication use (n=233), and controls were children with no history of wheezing and no diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 27 publications
5
30
1
1
Order By: Relevance
“…Yoneyama et al 13 also found that vaccination to BCG inhibits the development of atopic disorders. This is in contrast to reports by Anderson et al 5 and Wickens et al 4 who found no significant associations of atopy or asthma and the various childhood vaccinations investigated in this study. However, most of the previous studies were limited by either weak design (ecological studies, e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Yoneyama et al 13 also found that vaccination to BCG inhibits the development of atopic disorders. This is in contrast to reports by Anderson et al 5 and Wickens et al 4 who found no significant associations of atopy or asthma and the various childhood vaccinations investigated in this study. However, most of the previous studies were limited by either weak design (ecological studies, e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…There is a controversy about gender and asthma. Some authors suggested a positive association (Guilbert & Krawiec, 2003;Ronmark, Jonsson, Platts & Lundback, 1999;Chatkin, Menezes, Victora & Barros, 2003 and Anonymous-2-(n.d.) While others did not find any association (Wickens et al, 2002;Alba &Alsina, 1999 and Ece et al, 2000).The explanation of gender variation in relation to the childhood asthma is not clear. Cultural habits of our society to keep females more indoor and being less exposed to the outdoor environment may play a role in this respect.…”
Section: Resultsmentioning
confidence: 89%
“…Cultural habits of our society to keep females more indoor and being less exposed to the outdoor environment may play a role in this respect. In addition, infection among females during infancy and childhood may protect them against asthma (Partridge &Alwan, 1997 andWickens et al, 2001).With respect to the crowding status illustrated in table 1, we could see that the prevalence of asthma is increasing steadily (27.4%, 28.3%, 39.5%) with increased crowding rate (CR) (<3, 3 -5, >5) respectively. And statistically significant association has been found between CR and asthma (χ 2 = 9.52, P=0.009).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…3 In international studies, English speaking countries have been identified as having high rates of selfreported asthma symptoms in children, with New Zealand having the highest rate. [4][5][6][7][8][9] National and international guidelines for treatment have changed from being based on asthma severity to gaining control of symptoms through a stepwise escalation of medication, maintaining the lowest level of medication that controls asthma symptoms. [10][11][12] Two outcomes indicating poor symptom control and/or inadequate treatment for asthma are hospital admissions for asthma and oral steroid treatment.…”
Section: Introductionmentioning
confidence: 99%